VALUE-BASED APPROACH TO MANAGING CURRENT ASSETS OF CORPORATE CONSTRUCTION COMPANIES - Galyna Shapoval; Oleksandr Vashchenko (Сучасний стан наукових досліджень та технологій в промисловості)
In modern conditions of management, the value of an enterprise becomes the main indicator, which is learned not only by scientists, but also by owners of enterprise and potential investors. Current assets take a very important place among the factors that affect the value of an enterprise, so management of current assets becomes more acute from the point of their impact on enterprise value. The purpose of the paper is to develop a system of value-based management of corporate construction companies’ current assets. The main tasks are: the study of current assets impact on the value of corporate construction companies, the definition of value-based approach to managing current assets of corporate enterprises and development of value-based management system of corporate construction companies’ current assets by elements. General scientific and special research methods were used while writing the work. Value-based management of current assets involves value-based management of the elements of current assets. The value-based inventory management includes the following stages of management: the assessment of reliability and choice of supplier according to the criterion of cash flow maximization, the classification of stocks in management accounting according to the rhythm of supply and the establishment of periodicity of supplies in accordance with the needs of the construction process. The value-based management of accounts receivable includes the following stages of management: assessment of the efficiency of investment of working capital into accounts receivable, the assessment of customers' loyalty and the definition of credit conditions and monitoring of receivables by construction and debt instruments. Value-based cash management involves determining the required level of cash to ensure the continuity of the construction process, assessing the effectiveness of cash use according to the criterion of maximizing cash flow, as well as budget formation and control of cash flow. Value-based management of current assets of corporate construction companies is the development of targeted actions to optimize inventories, accounts receivable and cash, in order to ensure cash flow generation, and, accordingly, increase the value of the enterprise, which will ensure the growth of the welfare of owners. Applying a value-based approach to the management of current assets of corporate enterprises in the construction industry will allow reducing costs and net working capital of the enterprise by optimizing the size of inventories and receivables, which will lead to an increase in cash flow and value of enterprises.